FAKTOR-FAKTOR PENYEBAB TERJADINYA CERAI-GUGAT DI PENGADILAN AGAMA BEKASI - Raharjo, Tito; Hambali, Yoyo (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2017)
The purpose of research in writing this thesis is to determine the factors causing the divorce in the Bekasi Religious Court. Research using field research method in Bekasi Religious Court. The method of collecting data by means of observation, interviews, and study data documentation that has been collected processed and analyzed descriptively and analytically. The results showed that factors causing divorce in the Bekasi Religious Court in two years of 2013 and 2014 are polygamy, moral crisis, jealousy, forced marriage, physical and mental violence, biological defects, and economic factors. Of these factors, the most dominant factor, the cause of divorce is the economic factor.